Proposição metodológica para avaliação da implementação de planos diretores de recursos hídricos - Allan de Oliveira Mota (2018)
The Water Resources Plans (WRP) are management tools foreseen in the National Water Resources Policy, composed of diagnosis, prognosis and action plan. Minas Gerais has 30 Water Resources Management Plans (WRMP) concluded between 2006 and 2015, with short, medium and long term actions. The implementation of the planned actions can not always follow the established schedule, facing problems of planning, management and advice. The present study proposes a methodology to evaluate the degree of implementation of the Water Resources Plans through the elaboration of indicators of implementation of the actions and an index that allows the comparison of the degree of implementation among PRH. Indicators and the UPGRH characterization index were also proposed to assess the carrying capacity of their characteristics. The process of formulating the indicators and the index was attended by specialists in the area of planning and shared management of water resources. The indicators and the indices of implementation and characterization were applied in the WRMP and WRP of Rio das Velhas and the results pointed to a poor implementation condition and a good characterization condition, respectively. The analysis of the results also made it possible to search for correlations between the characteristics of the mentioned hydrographic basin and the degree of implementation of Water Resources Management Plan. The analysis of the degree of implementation of the PDRH will subsidize the water management of the state, collaborating with the decision-making of the managers and the members of the river basin committees. It will be possible to identify which actions or programs need the most attention and which characteristics should be replicated in the river basins by favoring the implementation of the Action Plan